Posts-tructuralism as alternative social science in Malaysia = Pasca-strukturalisme sebagai sains sosial alternatif di Malaysia - Ahmad, Khairil Izamin (2016)
Introduction - In this paper, I consider an interim vision of a social science in Malaysia that departs from traditional, mainstream approaches. A major point of discussion within the realm of social sciences in Malaysia has revolved around the need to develop a social science that considers epistemological problems pertaining to the adoption of approaches inspired by Western scientific influence (Rustam and Norani), and one that is able to provide a robust theoretical and methodological platform on which social scientific research can rest. In order to meet this challenge, the present dynamics within the social sciences in Malaysia must be deconstructed. Overwhelmingly, this dynamics is shaped, on the one hand, by works that invest heavily in normative presuppositions – either by ways of invoking the virtues of policies and measures that are pursued by the establishment, or critiquing such policies and measures from contending perspectives – and on the other, by works that assume neutrality and objectivity in analysing social phenomena, with a heavy emphasis on empiricism, driven by the positivist and behaviourist paradigms. And, while there have been efforts to reconsider the fundamental problems surrounding the applications of those paradigms, they remain at the level of epistemological critique.